The pressure of wildcat strikes on the transformation of industrial relations in a developing country: The case of the garment and textile industry in Vietnam. (April 2015) - Cox, Anne
Focusing on seven organizations, one from Hong Kong, three South Korea, and three Taiwan, operating in the garment and textile industry, this paper argues that the transformation of the Vietnamese industrial relations system has had very limited impact on the nature and capacity of trade unions. At the workplace level, the 'race to the bottom' has led to violations of labor rights. In this context, unofficial worker representatives (UWRs) have emerged and gained significant power to coordinate large scale strikes across firms and inter-provinces. This paper provides a clear profile of UWRs and shows that the bottom-up pressure created by wildcat strikes has influenced labor legislation and improved working conditions. The unofficial representation mechanism in Vietnam presents a unique example where an effective representation mechanism can be achieved without the presence of 'input legitimacy'. Furthermore, this paper argues that rapid industrialization and social transformation coupled with the increasing structural power of capital have escalated labor conflicts and strikes in Vietnam. It underlines the importance of involving workers and their representatives, be it official or unofficial, in the process of change and transition.